Auditoría de gestión al gobierno parroquial de Los Encuentros, provincia de Zamora Chinchipe, periodo 01 de enero al 31 de diciembre del 2011 - Vivanco Armijos, Melania Patricia (2015)
This thesis called "AUDIT MANAGEMENT GOVERNMENT PARISH OF MATCHES, PROVINCE OF ZAMORA CHINCHIPE, PERIOD 01 JANUARY TO 31 DECEMBER 2011", whose main objective was addressed to the implementation of the Management Audit by applying indicators management, with which it was determined the efficiency and cost effectiveness with which human talents of the audited entity are administered. The purpose of the audit was to analyze and evaluate the activities of the Vestry "Los Encuentros" to determine the efficiency and effectiveness of financial and human resources; the quality of service provided to the community and users of the period aforesaid, and establish the degree of compliance with existing laws. The objectives proposed in this investigation were met in full, efficiency, effectiveness and economy that can reflect them in the implementation of management indicators. The Board does not have the implementation of all internal control standards, poor management in implementing projects, no indicators are applied; so the audit becomes important tool for evaluating the management of public resources, in order to detect deviations and take the necessary corrective measures that seek compliance with institutional goals and objectives, improve services to the community. The objectives in this research were met in full, efficiency, effectiveness and economy that can reflect them in the implementation of performance indicators